'Cautiously optimistic': Older parent-carers of adults with intellectual disabilities – Responses to the Care Act 2014. (September 2019) - Gant, Valerie; Bates, Claire
This article discusses potential opportunities for best practice in the United Kingdom that may be brought about by the Care Act (2014). Carers in the United Kingdom were given new rights within this legislation with a focus on needs led assessment. The underpinning philosophy of the Care Act is to streamline the previous legislation and offers a framework for carers and people in receipt of care, to enable a more personalized approach to care and support. Offering a discussion of likely opportunities brought about by provisions of the Care Act, this article draws on a small study involving older parent/carers of sons or daughters with intellectual disabilities. Exploring the extent to which such parents of adults with intellectual disabilities were aware of the details of this legislation and the potential impact it may have on their lives highlighted other significant areas, some of which are discussed below. Semi-structured interviews were conducted with five parents over the age of 60 of sons or daughters with intellectual disabilities in North West England. The study adds to the body of knowledge and understanding about parents of adults with intellectual disabilities and explores and provides a deeper understanding of parents' experiences of the implementation of this specific piece of legislation and their perception of the relevance of it to themselves. Findings include some awareness of the legislation and some feelings of optimism about its likely implications, although participants appeared less clear about the specificities and the impact of these upon them and/or their sons or daughters. Findings from the semi-structured interviews also showed parent's articulation of the extent of reciprocal care manifest between them and their son or daughter with an intellectual disability, as well as an awareness of the fragility of their own emotional well-being.